Safety and efficacy of thoracic external beam radiotherapy after airway stenting in malignant airway obstruction - Rochet, Nathalie; Hauswald, Henrik; Schmaus, Martina; Hensley, Frank W.; Eberhardt, Ralf; Herth, Felix; Debus, Jürgen; Neuhof, Dirk (International journal of radiation oncology, biology, physics, 2012)
Purpose We retrospectively evaluated the outcome and toxicity of external beam radiotherapy (EBRT) after airway stents were placed in patients treated for malignant airway obstruction. Methods and Materials Between 2004 and 2009, we performed airway stenting followed by EBRT in 43 patients for symptomatic primary lung cancer (n = 31) or other thoracic malignancies (n = 12). The median time interval between stent placement and first irradiation was 14 days. A median total dose of 50 Gy was delivered. Sixty-seven percent of the patients had reduced performance status (Karnofsky performance score, ≤70). Results EBRT had to be stopped prematurely in 16 patients (37%), at a median total dose of 17 Gy, for various reasons. In this group of patients, the survival was poor, with a median overall survival (OS) of only 21 days. Twenty-seven patients (63%) completed radiotherapy as planned, with a median OS of 8.4 months. Fourteen of 43 patients (33%) developed at least one Common Terminology Criteria for Adverse Event of grade 3 to 5. The most common event was a malignant restenosis of the stent leading to asphyxia (n = 7), followed by fistula formation (n = 4), necrosis (n = 3), mediastinitis with abscess (n = 1), secondary nonmalignant airway stenosis (n = 1), and hemoptysis (n = 1). With the exception of one event, all events were associated with a local progression of the tumor. Conclusions Although the long-term prognosis for patients with malignant airway obstruction is poor, airway stenting combined with EBRT offers a possible therapeutic option, achieving fast relief of acute respiratory distress with an associated antitumor effect, resulting in a potential survival benefit. However, due to local advanced tumor growth, increased rates of adverse events are to be expected, necessitating careful monitoring.